Fracture mechanisms in Ti and Co–Cr growing rods and impact on clinical practice. (September 2021) - Ribesse, Arnaud; Ismail, Karim; Croonenborghs, Maïté; Irda, Nadia; Miladi, Lotfi; Jacques, Pascal J.; Mousny, Maryline; Pardoen, Thomas
Abstract: The widely used treatment of early onset scoliosis based on fusionless spinal instrumentation with growing rods suffers from severe complications due to premature rod failure. Only few studies have explored the fracture mechanisms in single rod constructs, while clinical practice urgently needs guidance. The objectives of this study are (i) to determine the failure mechanisms in Ti–6Al–4V alloy, Ti Cp 2 and Co–Cr alloy rods, and (ii) to propose strategies to reduce the risk of rod fracture. For this purpose, seven rods from three patients treated for early onset scoliosis were characterized by preoperative, pre-fracture X-rays and after-fracture X-rays. Fracture surface analysis, performed using scanning electron microscopy, revealed similar failure mechanisms for all rods, independent of composition and diameter. Fracture is caused by fatigue, associated to repeated bending action in the anteroposterior direction. Cracking initiates at multiple sites. Three-point bending fatigue tests on Ti–6Al–4V bent rods confirmed the fracture scenario. A beam bending model indicates that the failure process is controlled by the combination of cyclic vertical and horizontal forces with amplitudes from 200 N to 400 N and from 70 N to 150 N, respectively. Strategies to minimize fracture involve adaptations of material properties and rod geometry to scoliosis characteristics, including sagittal alignment, and spine behavior. Graphical abstract: Image 1